Bagatzi ECondHotel: Condominium/Ecological Hotel - Rojas Varela, Kevin (2016)
This condo / hotel was designed under high standards of bioclimatic architecture design to achieve maximum comfort with the lowest energy expenditure, taking advantage of the climatic conditions of the environment by transforming passive external elements -wind, water and vegetation- to produce internal comfort. In addition to an integrated design, it considers zoning based on wind, sun exposure and topography as well as the design of facades and devices to control climatic conditions given on the site.